AN EVIDENTIARY MANAGEMENT OF MEDICAL ERROR ELEMENTS IN THE FIELD OF BEAUTY AND AESTHETICS - Henry Jimmy Gultom; Irman Halawa; Redyanto Sidi (Jurnal Ekonomi, 2023)
The development of beauty and aesthetic service practices began with the practice of beauty salons and then developed into a medical action service in the field of beauty and aesthetics. Medical action in the field of beauty and aesthetics is different from medical services in general, in the legal procedures of health services, the patient's desire for beauty and aesthetic actions. That relating to the fulfillment and proof of the elements of guilt in medical crimes has its own characteristics with other criminal cases. It is necessary to regulate the competence of medical personnel who have clinical authority in the field of beauty and aesthetics so that the regulation of this authority provides protection and legal certainty for the community. Furthermore, in the service of medical actions in the field of beauty and aesthetics, legal reforms must also be carried out relating to surgical actions in the field of beauty and aesthetics that can change a person's identity.